MAKNA RITUAL PADA TRADISI DOA PADANG DI DESA SEBERANG GUNUNG KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Azizah, Nur; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The doa padang tradition in Seberang Gunung Village, Gunung Toar District, Kuantan Singingi Regency is a customary ritual performed before farming that contains rich cultural, spiritual, and social values. This study aims to analyze the meanings of rituals and symbols in the doa padang tradition and its role in strengthening the community’s social cohesion. The research uses a descriptive qualitative method with seven informants selected purposively through interviews, observation, and documentation, with data validity tested through triangulation. The results show that doa padang functions not only as a religious ritual but also as a form of symbolic communication that reinforces social relationships, spirituality, and cultural identity. The ritual consists of three main sta pre-ritual, implementation, and post-ritual each reflecting the values of togetherness, gratitude, and solidarity within the community. Cultural symbols such as dulang, calempong, traditional food, prayers, customary advice, and the Kuantan Malay language hold social and spiritual meanings that illustrate the harmony between humans, nature, and God. Based on George Herbert Mead’s Symbolic Interactionism theory, this tradition serves as a medium of symbolic interaction that fosters collective awareness to preserve the community’s traditional, moral, and social values. Keywords: Ritual Meaning, Doa Padang, Tradition